Mushrooms: a food-based solution to vitamin D deficiency to include in dietary guidelines - Starck, Carlene; Cassettari, Tim; Wright, Jutta; Petocz, Peter; Beckett, Emma; Fayet-Moore, Flavia (Frontiers in Nutrition, 2024)
Vitamin D deficiency and insufficiency is a public health issue, with low dietary vitamin D intakes a contributing factor. Rates of vitamin D deficiency are 31% in Australia, and up to 72% in some regions globally. While supplementation is often prescribed as an alternative to additional sun exposure, complementary approaches including food-based solutions are needed. Yet, food-centric dietary guidelines are not always adequate for meeting vitamin D needs. Edible mushrooms such as Agaricus bisporus can produce over 100% of vitamin D recommendations (10 µg/day, Institute of Medicine) per 75 g serve (18 µg) on exposure to UV-light, with the vitamin D2 produced showing good stability during cooking and processing. However, mushrooms are overlooked as a vitamin D source in dietary guidelines. Our dietary modelling shows that four serves/week of UV-exposed button mushrooms can support most Australian adults in meeting vitamin D recommendations, and UV-exposed mushrooms have been found to increase vitamin D status in deficient individuals. While recent evidence suggests some differences between vitamin D2 and vitamin D3 in physiological activities, vitamin D2 from mushrooms can be part of a larger solution to increasing dietary vitamin D intakes, as well as an important focus for public health policy. Mushrooms exposed to UV represent an important tool in the strategic toolkit for addressing vitamin D deficiency in Australia and globally. Health authorities lead the recognition and promotion of mushrooms as a natural, vegan, safe, and sustainable vitamin D food source.